SYNTHESIS AND CHARACTERIZATION OF SULFONATED POLYSULFONE FOR FUEL CELL APPLICATION - JAYUSMAN (NIM 10504076), YUYUS
The usage of fossil fuels as energy sources increases rapidly year by year that might lead to a crisis of energy. Therefore it is required a new alternative of energy such as fuel cell. In the field of portable devices, polymer electrolyte membrane fuel cell (PEMFC) is the best solution. Until now, Nafion® still is a membrane standard for PEMFC but its wide application is limited by its production cost. Thus it is necessary to look for some alternatives which are cheaper but their performance is not much less than Nafion®. In this research, the sulfonated polysulfone (SPSf) membranes were synthesized by homogeneous method using chlorosulfuric acid (ClSO3H) as sulfonating agent. Synthesis of SPSf was optimized by varying the concentration of ClSO3H. Synthesized membranes were characterized using FTIR spectrophotometer and determined their contact angle (CA), swelling degree, ion exchange capacity (IEC), degree of substitution (DS), proton conductivity, and membranes potential. The presence of SO3H groups in polysulfone (PSf) polymer chain is revealed by peak at 1028 cm-1 of IR absorption spectra while the widening of peak at 3385-3420 cm-1 indicates O-H stretching mode of SO3H groups. The swelling degree and contact angle results show that the membranes are hygroscopic. The IEC, DS, proton conductivity, and membranes potential are tended to increase with the concentration of ClSO3H.